A company application of the Balanced scorecard method to improve performance and gain competitive advantage - Qamar, Asad (2010)
Balanced Scorecard was introduced in the year 1992 by Robert Kaplan and David Norton. Previously emphasis was laid on the financial perspective. But with the introduction of balanced scorecard, non-financial measures were also given due importance. In addition to balanced scorecard there are many other performance measurement techniques. This study critically examines, that financial measures alone are not adequate for a firm. Looking at the future, financial measures play a very limited role and those companies relying solely on financial measures tend to maximize short term financial performance without thinking about future. I would be evaluating the performance of Exxon Mobil from the four perspectives of Kaplan and Norton through various techniques like running regression, and accounting interpretation of the performance at a time of corporate turnaround. Various measures from the four perspectives would be integrated with each other and a conclusion would be made whether the balanced scorecard application in the company was a successful one or not, in terms of performance measurement.